Enora Le Quéré, Les Cyclades sous l’Empire romain: Histoire d’un renaissance. pp. 456, b/w ills. 2015. Rennes: Presses Universitaires de Rennes (Collection: Histoire). ISBN 978-2-7535-4045-3, paperback €23 - Karambinis, Michalis (Journal of Greek Archaeology, 2020)
This is the fourth book dedicated to the Cyclades during the Roman period, after P. Nigdelis’ Πολίτευμα και Κοινωνία των Κυκλάδων κατά την Ελληνιστική και Αυτοκρατορική Περίοδο, Thessaloniki (University of Thessaloniki) 1990, L. Mendoni’s and S. Zoumbaki’s Roman Names in the Cyclades. Part I, Athens (National Hellenic Research Foundation) 2008, and S. Raptopoulos’, Κυκλάδες Νήσοι: Συμβολή στην Οικονομική τους Ιστορία κατά την Ελληνιστική και Αυτοκρατορική Εποχή, Tripolis (Archaeological Institute of Peloponnesian Studies) 2014. Le Quéré’s book essentially updates that of Nigdelis. Mendoni’s and Zoumbaki’s study is a catalogue of Roman names, while Raptopoulos’ work has clearly a more archaeological perspective.